2018
DOI: 10.20319/pijss.2018.33.11861202
|View full text |Cite
|
Sign up to set email alerts
|

Articulated Difficulties of Grade 11 Students at Taytay Senior High School (Tshs) in English Proficiency

Abstract: English has been the medium of instruction since the beginning of the 20th century in thePhilippines during the arrival of the Americans. This has been incorporated holistically in the society through the educational system, communication, mass media, publications and social media. It is given therefore that Filipino learners are bilingual--i.e., speaking both Filipino (the native tongue) and English as Second Language (ESL). After a century though, proficiency in the language is still a difficulty and an anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The concluded PISA 2018 was participated by OECD members as well as non-member nationstallying 79 countries in total. Thus, the aim of the test is to offer comparable data that would each country a chance to benchmark its education system against other countries in order to improve, enhance, and recalibrate on education policies, practices, objectives, and aims [10]. Apparently, Filipino pupils took part in PISA for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…The concluded PISA 2018 was participated by OECD members as well as non-member nationstallying 79 countries in total. Thus, the aim of the test is to offer comparable data that would each country a chance to benchmark its education system against other countries in order to improve, enhance, and recalibrate on education policies, practices, objectives, and aims [10]. Apparently, Filipino pupils took part in PISA for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…While it exhibited similar results to Manuel's [8] study, where students were revealed to be proficient users of English and excelled in reading comprehension, precisely the literal level, students tend to overly estimate their proficiency, particularly in the study of Ong and Villegas [55] where a majority of the students were unaware of using English incompetently. In addition, Blas et al [56] pointed out that many public senior high school students still had English language problems in reading, writing, speaking, and listening. Common culprits of students' problems in English were anxiety [55], subjects' complexity, training and knowledge, vocabulary, confidence, self-esteem, and interest [56,57].…”
Section: Level Of English Language Problemsmentioning
confidence: 99%
“…In addition, Blas et al [56] pointed out that many public senior high school students still had English language problems in reading, writing, speaking, and listening. Common culprits of students' problems in English were anxiety [55], subjects' complexity, training and knowledge, vocabulary, confidence, self-esteem, and interest [56,57]. This suggests that the English language problems of senior high school students in the Philippines vary in the context of private and public institutions.…”
Section: Level Of English Language Problemsmentioning
confidence: 99%
“…One of the important issues addressed in the present study are the topics and targeted competencies in the Reading and Writing curriculum being "idealistic, complex, and demanding" (Jaca et al, 2019, p.309), giving students very high expectations in the absence of acknowledging their context. Additionally, it is necessary to note that beyond the Reading and Writing curriculum, proficiencies in reading and writing has proven to be a struggle among students for those skills are not readily available to ESL/ESL learners due to the complex nature of those skills (Atanacio-Blas et al, 2018;Farkas & Jang, 2019;Graham, Harris, & Beard, 2019;Gustilo & Magno, 2015;Gustilo, 2013;Hall, 2012;Nueva, 2016;Nusrat, 2016;Sadeghi, 2007;Tenri Ampa & Quraisy, 2017). In this light, Pablo and Lasaten (2018) offered an explanation to the situation explaining that the learners' diversity in terms of their sociocultural background, coupled with their varied linguistic backgrounds, results to students' difficulties in English.…”
Section: Introductionmentioning
confidence: 99%